The role of COSO framework in preventing earning management practice An analytical study of the opinions of a sample of Auditors & Accountants in banks- Erbil City - Shadan Jabbar Abdulfattah (Zanco Journal of Humanity Sciences)
The main objective of this study is to determine the effectiveness of internal control according to the COSO framework for internal control contributes to reducing earning management practices in banking sectors in Erbil city from the point of view of auditors and accountants through quantitative measurement of variables.